PENGARUH KEPERCAYAAN MEREK, KEAMANAN DAN PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN ONLINE(Studi Pada Ibu Rumah Tangga di DKI Jakarta) - Nida Amalia Fadhillah (2023)
This study uses quantitative methods with the aim of proving the influence of brand trust, safety, and consumer behavior both directly and indirectly on purchasing decisions. This study used 100 housewife respondents in DKI Jakarta as primary data and secondary data researchers obtained through various references related to research. Data were collected using purposive sampling technique and analyzed using descriptive and inferential analysis techniques with the help of SmartPLS software. So that data processing obtains the results that (1) Brand Trust has a positive and significant effect on Purchase Decisions, (2) Security has a positive and significant effect on Purchase Decisions, (3) Consumer Behavior has a positive and significant effect on Purchase Decisions.